The West African experience in establishing steering committees for better collaboration between researchers and decision-makers to increase the use of health research findings - Namoudou Keita; Virgil Lokossou; Abdramane Berthe; Issiaka Sombie; Ermel Johnson; Kofi Busia (BMC, 2017)
Abstract Background Aware of the advantages of a project steering committee (SC) in terms of influencing the development of evidence-based health policies, the West African Health Organisation (WAHO) encouraged and supported the creation of such SCs around four research projects in four countries (Burkina Faso, Nigeria, Senegal and Sierra Leone). This study was conducted to describe the process that was used to establish these committees and its findings aim to assist other stakeholders in initiating this type of process. Methods This is a cross-sectional, qualitative study of the initiative's four projects. In addition to a literature review and a review of the project documents, an interview guide was used to collect data from 14 members of the SCs, research teams, WAHO and the International Development Research Center. The respondents were selected with a view to reaching data saturation. The technique of thematic analysis by simple categorisation was used. Results To set up the SCs, a research team in each country worked with health authorities to identify potential members, organise meetings with these members and sought the authorities' approval to formalise the SCs. The SCs' mission was to provide technical assistance to the researchers during the implementation phase and to facilitate the transfer and use of the findings. The 'doing by learning' approach used by each research team, combined with WAHO's catalytic role with each country's Ministry of Health, helped each SC manage its contextual difficulties and function effectively. Conclusion The involvement of technical and financial partners motivated the researchers and ministries of health, who, in turn, motivated other actors to volunteer on the SCs. The 'doing by learning' approach made it possible to develop strategies adapted to each context to create, facilitate and operate each SC and manage its difficulties. To reproduce such an experience, a strong understanding of the local context and the involvement of strong partners are required.